2021
DOI: 10.1108/srj-02-2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

Employee-level consequences of perceived internal and external CSR: decoding the moderation and mediation paths

Abstract: Purpose This paper aims to examine whether and how internal and external typologies of corporate social responsibility (CSR) and employees’ CSR participation (CSRP) differentially impact organizational citizenship behavior (OCB) and turnover intentions (TI), mediated by meaningful work (MW) and affective commitment (AC) and moderated by CSR motive attributions. Design/methodology/approach Bootstrapped structural equation modeling using AMOS and mediation and moderation analysis using Hayes’ Process macro in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 163 publications
(306 reference statements)
0
7
0
Order By: Relevance
“…After a thorough investigation, published empirical research papers exhibiting the relationship between cohesion and virtual team performance were considered. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) was designed meta-analysis (Gonçalves et al , 2015; Aggarwal and Singh, 2021) and Meta essential was used 1.5 for analysing its output. Meta-Essentials 1.5, user-friendly software for meta-analysis, was used to generate the data, figures and tables (Suurmond et al , 2017).…”
Section: Methodsmentioning
confidence: 99%
“…After a thorough investigation, published empirical research papers exhibiting the relationship between cohesion and virtual team performance were considered. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) was designed meta-analysis (Gonçalves et al , 2015; Aggarwal and Singh, 2021) and Meta essential was used 1.5 for analysing its output. Meta-Essentials 1.5, user-friendly software for meta-analysis, was used to generate the data, figures and tables (Suurmond et al , 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, empirical evidence of how the external publics perceive these two types of statements is still lacking. Moreover, research has suggested that there are different mechanisms underlying people's perceptions of corporate CSR communication on external versus internal actions, which can lead to differential outcomes of these two types of corporate statements (Aggarwal and Singh, 2023; Chen et al , 2022; Hameed et al , 2016).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Cluster 6: Gender Diversity on Board and Firm Performance The sixth cluster, on the theme of board gender diversity and firm performance, is represented by light blue colour. This theme has received wide curiosity in recent years (Baker et al, 2021;Singh et al, 2021). The cluster comprises three seminal articles evaluating the impact of gender diversity on firm performance (Adams & Ferreira, 2009;Bhagat & Bolton, 2008;Campbell & Mínguez-Vera, 2008).…”
Section: Co-citation Analysismentioning
confidence: 99%
“…Apart from the theme of gender diversity and firm performance, other themes such as gender diversity and corporate social responsibility (Singh et al, 2021), and sustainability (Al-Shaer & Zaman, 2016) have also been explored in recent years.…”
Section: Co-citation Analysismentioning
confidence: 99%
See 1 more Smart Citation